Seizing the momentum to reshape agriculture for nutrition - Fan, Shenggen; Yosef, Sivan; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2019)
Throughout most of the 20th century, the main focus of agricultural efforts was addressing food shortages by increasing production. Up until the 1980s, most economists still focused solely on strategies to produce more energy to meet consumer demand, under the assumption that nutrition did not play a role in consumer preferences. In the 1990s, a small segment of the development community began to explore the links between agriculture and nutrition on a wider scale. The past decade has seen even greater momentum in the agriculture-nutrition field. The power of the conceptual links between agriculture and nutrition has increasingly been probed by researchers. Numerous policy platforms and mechanisms have been established to address agriculture and nutrition both directly and indirectly. Small and large organizations have begun integrating agriculture and nutrition in programming, monitoring, and evaluation. This chapter focuses on the advances made in these areas during the past 5-10 years to review what has changed, and what has not.